Ekspansja zagraniczna koncernu Volkswagen - Sobotkiewicz, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article presents foreign expansion of an international enterprise - the Volkswagen concern. The author focuses on characteristics of the concern enterprises and presentation of Volkswagen car sale value between 2003 and 2006 in the world divided into continents. Furthermore, the author identifies main countries, where is the biggest demand for the concern cars, and employment state of grouping in several countries in the world, where the concern runs its activity.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 611-621